Does biodiversity‐focused protection of the seabed deliver carbon benefits? A U.K. case study. Issue 1 (22nd November 2022) - Epstein, Graham; Roberts, Callum M.
Abstract: Subtidal seabed sediments are one of the planet's biggest organic carbon stores, but have been poorly considered in nature‐based climate change mitigation. Protection of the seabed is predominantly through establishment of marine protected area (MPA) networks, but their emphasis on biodiversity may limit their carbon value. The United Kingdom has one of the most extensive networks of MPAs in the world, yet damaging human activities are excluded from only a small portion. We calculate that full protection of the MPA network would offer limited carbon benefit, due to below average organic carbon stocks and disturbance from mobile fishing gears when compared to the entire U.K. seabed. We find that inshore exclusion zones (where mobile gears are restricted from nearshore areas to benefit biodiversity and low‐impact fishers) could offer greater carbon benefits compared to MPAs. However, neither of these biodiversity‐focused protection strategies are as effective for seabed carbon as targeted protection.